Fungal diversity associated with Hawaiian Drosophila host plants. - Brian S Ort (Public Library of Science (PLoS), 2012)
Hawaiian Drosophila depend primarily, sometimes exclusively, on specific host plants for oviposition and larval development, and most specialize further on a particular decomposing part of that plant. Differences in fungal community between host plants and substrate types may establish the basis for host specificity in Hawaiian Drosophila. Fungi mediate decomposition, releasing plant micronutrients and volatiles that can indicate high quality substrates and serve as cues to stimulate oviposition. This study addresses major gaps in our knowledge by providing the first culture-free, DNA-based survey of fungal diversity associated with four ecologically important tree genera in the Hawaiian Islands. Three genera, Cheirodendron, Clermontia, and Pisonia, are important host plants for Drosophila. The fourth, Acacia, is not an important drosophilid host but is a dominant forest tree. We sampled fresh and rotting leaves from all four taxa, plus rotting stems from Clermontia and Pisonia. Based on sequences from the D1/D2 domain of the 26S rDNA gene, we identified by BLAST search representatives from 113 genera in 13 fungal classes. A total of 160 operational taxonomic units, defined on the basis of ≥97% genetic similarity, were identified in these samples, but sampling curves show this is an underestimate of the total fungal diversity present on these substrates. Shannon diversity indices ranged from 2.0 to 3.5 among the Hawaiian samples, a slight reduction compared to continental surveys. We detected very little sharing of fungal taxa among the substrates, and tests of community composition confirmed that the structure of the fungal community differed significantly among the substrates and host plants. Based on these results, we hypothesize that fungal community structure plays a central role in the establishment of host preference in the Hawaiian Drosophila radiation.